PENGARUH FRAUD TRIANGLE THEORY TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Rinda Harunsari; Sarah Yuliarini (Jurnal Ilmiah Akuntansi, 2025)
Management manipulates financial statements to produce reports that do not reflect the actual condition. This practice has become increasingly common, including among pharmaceutical companies listed on the Indonesia Stock Exchange. The Fraud Triangle theory proposed by Donald Cressey (1953) includes the element of pressure, represented by financial targets (ROA) and external pressure (LEV); opportunity, represented by industry nature (Receivable); and rationalization, represented by total accruals to total assets (TATA). This study examines four factors suspected of influencing financial statement fraud. Fraud is measured using the Beneish M-Score to detect indications of report manipulation. Using a quantitative method and an associative research design, the sample consists of 24 pharmaceutical companies listed on the Indonesia Stock Exchange during 2021–2023, resulting in 72 observations selected through purposive sampling. Analysis using binary logistic regression in SPSS 26 shows that industry nature (Receivable) and rationalization (TATA) affect financial statement fraud. In contrast, financial targets (ROA) and external pressure (LEV) do not affect financial statement fraud.